2019
DOI: 10.1038/s41419-019-1583-4
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomic analysis of human mesenchymal stem cells reveals limited heterogeneity

Abstract: Mesenchymal stem cells (MSCs) are a population of multipotent cells with a superior ability to promote tissue repair by regulating regeneration and inflammation. Effective application of MSCs in disease treatment relies on the production of relatively homogeneous cell population. However, the cellular heterogeneity and the differentiation trajectories of in vitro expanded MSCs remain largely unclear. We profiled the transcriptomes of 361 single MSCs derived from two umbilical cords (UC-MSCs). These UC-MSCs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 35 publications
10
81
2
Order By: Relevance
“…At sample level, one menstrual phase sample (M1) and one secretory phase sample (S3) manifested quiescent/senescence characteristic with a high proportion of cells at the G1 phase, whereas the remaining samples demonstrated a high proportion of cells in the proliferative phase ( Figure 1B). From overview of all single cells, PCA results based on normalized gene expression matrix showed that variance of the first 3 principal components were mainly caused by cell cycle effect ( Figure 1C) and batch/donor effect (Figure 1D), which were consistently observed in other single cell studies on MSCs [13][14][15]. The results indicated that unwanted major source of variation should be removed before investigation on the molecular heterogeneity of eMSCs.…”
Section: Variation Dominated By Cell Cycle and Donor Effect In Emscssupporting
confidence: 66%
“…At sample level, one menstrual phase sample (M1) and one secretory phase sample (S3) manifested quiescent/senescence characteristic with a high proportion of cells at the G1 phase, whereas the remaining samples demonstrated a high proportion of cells in the proliferative phase ( Figure 1B). From overview of all single cells, PCA results based on normalized gene expression matrix showed that variance of the first 3 principal components were mainly caused by cell cycle effect ( Figure 1C) and batch/donor effect (Figure 1D), which were consistently observed in other single cell studies on MSCs [13][14][15]. The results indicated that unwanted major source of variation should be removed before investigation on the molecular heterogeneity of eMSCs.…”
Section: Variation Dominated By Cell Cycle and Donor Effect In Emscssupporting
confidence: 66%
“…Recently, several studies have been performed to investigate into the heterogeneity of cultured MSCs by single-cell transcriptomic analysis [35,[81][82][83]. Huang et al profiled the transcriptomes of 361 single MSCs derived from two umbilical cords (UC-MSCs) that were harvested at different passages and stimulated with or without inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al profiled the transcriptomes of 361 single MSCs derived from two umbilical cords (UC-MSCs) that were harvested at different passages and stimulated with or without inflammatory cytokines. Following the analysis, they concluded that in vitro expanded UC-MSCs are a well-organized population with limited heterogeneity, which is mainly caused by distinct distribution in cell cycle phases [81]. However, the number of cells sequenced for each condition is small (~50 cells per condition), and they did not remove the cell cycle effects for the subpopulations identification.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have been performed to investigated into the heterogeneity of cultured MSCs by single cell transcriptomic analysis (Huang et al, 2019; Khong et al, 2019; Liu et al, 2019; Wang et al, 2019). Huang et al profiled the transcriptomes of 361 single MSCs derived from two umbilical cords (UC-MSCs) that were harvested at different passages and stimulated with or without inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al profiled the transcriptomes of 361 single MSCs derived from two umbilical cords (UC-MSCs) that were harvested at different passages and stimulated with or without inflammatory cytokines. Following analysis, they concluded that in vitro expanded UC-MSCs are a well-organized population with limited heterogeneity, which is mainly caused by distinct distribution in cell cycle phases (Huang et al, 2019). However, the number of cells sequenced for each condition is small (~50 cells per condition), and they did not remove the cell cycle effects for the subpopulations identification.…”
Section: Discussionmentioning
confidence: 99%